KEBIJAKAN 30% KETERWAKILAN PEREMPUAN DALAM DPRD MENURUT PERSPEKTIF ISLAM - Noviyanti Soleman; Rifki Elindawati (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2019)
Indonesia is one of the countries with the majority Muslim people in the world. Indonesia also joins to follow up the gender equality and women empowerment. One of the things is by increase the quota of women in house of representative. In case of Islam, most of the people are believe that the leader should be men. To assess this condition, this research aims to know the 30% women quota house of representative in Indonesia based on Islamic perspective.